Hypertension: prevalence, awareness, treatment and control in a rural area of North Kerala, India - R. K., Suma; T. R., Mayamol; Divakaran, Binoo; Karunakaran, Usha; A. K., Jayasree (International Journal Of Community Medicine And Public Health, 2017)
Background: High blood pressure is prevalent all over the world and is one of the major causes of cardiovascular morbidity and mortality. In considerable proportion of cases the disease tends to be asymptomatic for prolonged time, hence also labelled as “silent killer”. Awareness, treatment, and control of hypertension remain major challenges worldwide. The objective of this study was to determine the prevalence, awareness, treatment and control of hypertension in Northern Kerala. Methods: A community-based cross-sectional study among 687 subjects aged ≥20 years was conducted from March 2017 to July 2017. Data was collected by personal interviews, followed by anthropometric and blood pressure measurements. Diagnosis of hypertension was based on Joint National Committee (JNC) VIII guidelines. Results: The prevalence of hypertension (JNC VIII) was 48.2% with a 95% confidence interval ranging from 44.46% to 51.94%. Prevalence among males: 58.1% and females: 44.5%. Among the total hypertensives, 38.7% were aware. Of these, 94.5% taking treatment, 47.1% achieved adequate blood pressure control. Advancing age, current diabetic status, body mass index, and family history of hypertension were identified as risk factors for hypertension by multivariate logistic regression. Conclusions: High prevalence of hypertension was observed in the population. The low levels of awareness and control underscores the large gap between evidence and practice that needs to be bridged, for effective control of hypertension. This calls for plan to adopt preventive and control strategies and promote the health of the population.